Higher Education Institutions and Sustainable Development Implementing a Whole-Institution Approach - Rieckmann, Marco; Bormann, Inka (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sustainability is an urgent developmental task for our society and is attracting increasing attention. Therefore, higher education institutions (HEIs) are also called upon to deal theoretically, conceptually, methodically, critically, and reflectively with the associated challenges and the processes and conditions of transformation in order to contribute to sustainable development. How can complex organisations such as HEIs succeed in initiating and maintaining the process of sustainable development within their own institutions and make it a permanent responsibility? How can as many protagonists as possible be persuaded to get involved in sustainable development? This book deals with the promotion of sustainable university development and provides an overview of how universities can be organised sustainably and how sustainable development can be implemented in their various functional areas. In the sense of a "whole-institution approach", which encompasses entire HEIs, the focus is not only on the core areas of teaching (higher education for sustainable development) and research (sustainability in research) but, also, on the operational management of HEIs. In addition, this book focuses on sustainability governance and transfer for sustainable development at HEIs as cross-disciplinary issues.